2018
DOI: 10.1590/2177-9465-ean-2017-0442
|View full text |Cite
|
Sign up to set email alerts
|

Use of clinical simulation to improve diagnostic reasoning in nursing

Abstract: Objectives: Propose a methodology for the construction of simulated scenarios and cases to improve diagnostic reasoning in nursing. Method: A methodological study was conducted using theories and concepts from the dual processing theory to develop cases and scenarios of clinical simulation for diagnostic reasoning in nursing through proper use of analytical and non-analytical reasoning. Results and discussion: This study presents and discusses issues of the theoretical framework and operational elements: str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
0
14
0
17
Order By: Relevance
“…Clinical simulations enable the use of resources to provide training in psychomotor, cognitive, and affective skills, stimulating reflexive and critical thinking, clinical judgment, and decision making while avoiding real patients' exposure to danger (7)(8)(9) . It also improves knowledge, self-confidence, and learning satisfaction (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical simulations enable the use of resources to provide training in psychomotor, cognitive, and affective skills, stimulating reflexive and critical thinking, clinical judgment, and decision making while avoiding real patients' exposure to danger (7)(8)(9) . It also improves knowledge, self-confidence, and learning satisfaction (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, from the graphic organization of the words according to their frequency, the most prevalent terms appeared greater than the others (Figure 1). Therefore, it was found that the most cited words were no (27), being (23), simulation (22), knowing (14), practical (14), staying (13), when (10) and a lot (10).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical simulation provides the student with considerable learning, so that the undergraduate, as a spectator, becomes a co-participant in the setting in terms of developing their critical knowledge to build strategies that can intervene in the proposed case. 23 In this segment, simulation favored all research participants, including those graduating students who collaborated passively for research, since there was an interest by academics in analyzing the entire context of the case presented and, together with the other colleagues, outline the best strategy for the benefit of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors ( 8 , 11 , 15 , 21 ) report that learning depends on reflection and integration of the experience. Reflection can be taught with availability and active engagement, under the orientation from an effective debriefer.…”
Section: Discussionmentioning
confidence: 99%
“…During the debriefing, students have the opportunity to explore their emotions, identify their processes of thought, clinical judgment, and nursing conduct ( 8 ) . In this process, the teachers’ mediation must be planned and include considerations aimed at promoting reflective thinking to help students understand the correlations between patient data, clinical condition, and appropriate nursing conduct ( 8 - 11 ) .…”
Section: Introductionmentioning
confidence: 99%